Learning Organization and Work Engagement: An Empirical Evidence of a Higher Learning Institution in Malaysia - Hussein, Norashikin; Abdul Razak, Nurain Anis; Omar, Muhamad Khalil (Information Management and Business Review, 2017)
Rapidly changing business environment requires organization to gain competitive advantage in order to survive. As people is known to be the most valuable assets to an organization, having employees that are actively engaged in their work can positively leads to higher performance and subsequently contribute to the success of the organization. One of the factors that would lead to work engagement among employees is through the learning organization concept which provides continuous learning and improvement, directly linked to an employee daily work and development. Despite its importance, seldom has it been reported in the literature that this paradigm has been examined. Therefore, this study attempts to determine: (i) the level of work engagement among employees; and (ii) the relationship between learning organization dimension and work engagement. Data collected from 150 employees of an institution of higher education revealed that work engagement among employees is at high level. Only four learning organization dimensions namely, empowerment, embedded system, environmental connection and strategic leadership were found to have positive and significant relationships with work engagement. The implications and consequences of the study findings for higher learning institutions are further discussed.